Studi Potensi dan Nilai Ekonomi Berdasarkan Biaya Perjalanan dan Kesediaan Membayar di Pantai Sri Mersing Kabupaten Serdang Bedagai Potential Studies and Economic Value Based Travel Cost Method and Willingness To Pay in Sri Mersing Beach Serdang Bedagai - Febrina Astria Simanjuntak; Pindi Patana; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The beach is one of recreational attraction that people want to interact directly and enjoy the beauty of natural resources. Research was conducted at Sri Mersing Beach Serdang Bedagai from August to September 2014 by interviewing respondents that. Assessment of tourism Potential at Sri Mersing beach by using a modification of the ADO-ODTWA of the Forestry Department. Showed that Sri Mersing Beach Tourism has a great potential to be developed.Economic value was measured by Travel Cost Method (TCM) and willingness to pay. The results showed that the Travel Cost average is Rp. 116 273,- while The average cost of willingness to pay current existense is Rp. 5.568,- and after adding the facilities is Rp.14.090,-.Keywords: Economic Value, Willingness To Pay (WTP), Travel cost, Tourism, Beaches Sri Mersing.